2019
DOI: 10.14740/jocmr4021
|View full text |Cite|
|
Sign up to set email alerts
|

Asthma Control and Its Predictive Factors in Adult Asthma Patients

Abstract: BackgroundAsthma is a highly prevalent condition that remains difficult to control, as its associated factors remain poorly understood. Thus, the primary aim of the present investigation was to determine the prevalence of uncontrolled asthma in hospital units in south Jordan and to evaluate the risk factors that may contribute to uncontrolled asthma.MethodsThis was a cross-sectional study involving 93 patients aged 40.5 ± 13.6 years that met the criteria of the Global Initiative for Asthma (GINA). Relevant pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“…Interestingly, individuals who self-identified as black were not found to have a higher prevalence than white individuals, in contrast with current findings from asthma prevalence research 47 . The effect of age and prevalent asthma found in this study showed decreasing odds of asthma with increasing age, which does not seem to be biologically consistent nor does it appear to be consistent with the current body of research 48 and may be explained instead by a misclassification bias within the prevalence data. However, we did observe that the decreased prevalence in the diagnoses of asthma (from 8.2% for first quartile of age to 1.6% of fourth quartile of age).…”
Section: Discussioncontrasting
confidence: 74%
“…Interestingly, individuals who self-identified as black were not found to have a higher prevalence than white individuals, in contrast with current findings from asthma prevalence research 47 . The effect of age and prevalent asthma found in this study showed decreasing odds of asthma with increasing age, which does not seem to be biologically consistent nor does it appear to be consistent with the current body of research 48 and may be explained instead by a misclassification bias within the prevalence data. However, we did observe that the decreased prevalence in the diagnoses of asthma (from 8.2% for first quartile of age to 1.6% of fourth quartile of age).…”
Section: Discussioncontrasting
confidence: 74%
“…A study by ( 25 ) revealed that only 28.6% of the investigated physicians (general practitioners) have adequate knowledge regarding asthma, and only 10.4% of them had adequate practice in asthma management ( 25 ). A cross-sectional study by ( 26 ) reported that asthma control in Jordan was achieved in 45.2% of the study sample ( 26 ). Several other studies also reported poor management of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a large study in 2018 in the Middle East and North Africa reported that asthma was controlled in <30% of patients and it was attributed to poor adherence to prescribed medication, smoking, lack of medical insurance, and education level ( 28 ). Such results indicate that access to proper treatment, medication adherence, follow-ups by physicians, and education among healthcare providers and patients are mandatory to achieve better control of asthma ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Price et al reported more than 40% of asthma patients used their reliever medications three or more times in the previous week, which the author may judge the reason for the high levels of uncontrolled asthma [34]. Several studies also reported patients with severe asthma [12,[61][62][63], history of asthma exacerbations/hospitalizations [45,49,53,61,63,64], who had comorbid diseases [13,[50][51][52]65], smoking [43,52,66], oral corticosteroid use [12,63], and irregular follow-up visit [56,67] were more likely had a higher rate of uncontrolled asthma.…”
Section: Plos Onementioning
confidence: 99%